A critique of: Skepticism About Recent Evidence that Psilocybin Opens Depressed Minds - Carhart-Harris,R; Daws,RE; Nutt,D (2022)
This document details an authors' response to a critique of their work entitled: Skepticism About Recent Evidence that Psilocybin Opens Depressed Minds.